MODEL PEMBELAJARAN MEAN ENDS ANALISIS (MEA) DALAM MENINGKATKAN KEMAMPUAN LITERASI NUMERASI DI SD NEGERI 4 GIRIWOYO WONOGIRI - Satuti, Retno (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
Numeracy literacy refers to the knowledge and skills needed to understand texts and to use a variety of numbers and symbols to solve practical problems in various real-life contexts. In fact, the numeracy literacy skills of students at SDN 4 Giriwoyo remain low. To address this issue, teachers have implemented the Means Ends Analysis (MEA) learning model. This study aims to describe the preparation, implementation, and obstacles encountered by teachers in implementing the MEA model in mathematics learning as an effort to improve students' numeracy literacy skills in SD Negeri 4 Giriwoyo, Wonogiri. Using a qualitative approach, the study began with data collection through interviews and observations involving the principal, classroom teacher, and sixth-grade students. The collected data were then analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results of the study show that the preparation for the MEA learning model included the development of teaching modules, instructional materials, learning media, and assessment instruments. The implementation of the MEA model was carried out in three stages: introduction, main activities, and closing. Several challenges faced by teachers in implementing the MEA learning model were: 1) Difficulty in creating problem-solving questions; 2) Difficulty in designing problems that are easily understood by students; 3) Students experienced difficulties in solving the problems; 4) Students perceived the learning model as less enjoyable due to the complexity of the tasks; 5) Students with low math proficiency tended to be passive; 6) Creating mathematical problem-solving questions required careful thought; and 7) Students struggled to express mathematical problems clearly.